Implementation of Educational Technology to Increase Students' Learning Interest during Pandemic - Husaini, Aldi Al; Salsabila, Unik Hanifah; Salma, Hanifah; Harmita, Harmita; Santika, Dede (International Journal Labs, 2021)
Technology itself from time to time has increased significantly so that it can be utilized in various fields, especially in the field of education itself. In the midst of the COVID-19 pandemic, students are unable to take part in learning at school face to face with teachers. So here the role of educational technology is very important to apply. The purpose of this study was to determine the implementation of educational technology to increase student interest in learning during the pandemic. Research used literature research is combined with qualitative approaches. Research is conducted by collecting from various sources of literature from various journals and books that have a relationship with our research theme, namely the implementation of educational technology to increase students' learning interest in pandemic times. The application of educational technology acts as an effort to improve and launch the current online learning process, it can be said that educational technology is not only as bridging teaching and learning activities but becomes the heart of the process of ongoing activities.